A Bibliometric Analysis of Microalgal Omega-3 Fatty Acids - Eva Musifa (BIOVALENTIA: Biological Research Journal, 2026)
Microalgal omega-3 fatty acids have gained considerable attention as sustainable alternatives to fish-derived lipids due to environmental constraints, contamination risks, and increasing demand for nutraceutical products. However, the rapid growth of this field has led to a fragmented body of literature, necessitating a systematic evaluation of research trends and thematic developments. This study aims to examine the evolution, collaboration patterns, and thematic structure of microalgal omega-3 research using a bibliometric approach. Bibliographic data were retrieved from the Scopus database for the period 2010–2025 using relevant keywords, yielding 1,050 publications after screening. The dataset was analyzed using Biblioshiny and VOSviewer to assess publication trends, country contributions, journal distribution, author networks, and keyword co-occurrence. The results demonstrate a marked increase in publication output, particularly after 2017, indicating growing interest in sustainable lipid sources and functional food applications. India, China, and the United States emerged as leading contributors, supported by strong international collaboration. Thematic analysis identified four principal clusters: microalgal biotechnology and lipid production, nutritional and pharmaceutical applications, metabolic and biosynthetic pathways, and food and feed utilization. Therefore, this study highlights the rapid expansion and multidisciplinary nature of microalgal omega-3 research while providing insights to support future scientific development and innovation.